COMPUTER VISUALIZATION IN TEACHING GENERAL TECHNICAL DISCIPLINES: THEORETICAL AND PRACTICAL ASPECTS - Pohorielov, Mykhailo; Prasol, Artem (Visnyk universytetu imeni Alʹfreda Nobeli͡a︡. Serii͡a︡: Pedahohika i psikholohii͡a, 2024)
The article investigates the development of visual aids and visualization ideas in the organization of the educational process, particularly in teaching general technical disciplines. The article aims to review the development of visual aids and visualization ideas in education, clarify the essence of computer visualiza- tion, classify its types and kinds, and determine the directions of computer visualization usage in teaching general technical disciplines and the software applications that ensure their development for educational purposes. The study operates methods of retrospective, content, and semantic analysis, classification, gen- eralization, and modelling. The historical context of introducing electronic visualization tools in education has been considered in the study, starting from the first projectors in the 1930s to modern computer visualization technologies such as 2D and 3D visualization, stereoscopic 3D, virtual reality (VR), and augmented reality (AR). The es- sence of computer visualization as a general term for graphic methods of creating, analysing, and transmit- ting information has been defined. Differences between the didactic principles of visual aids and visualiza- tion have been clarified. It has been highlighted that visualization has a more complex structure since it in- cludes actions for constructing images of investigated objects or phenomena. The article identifies the directions for implementing computer visualization, including scientific, soft- ware, and information visualization. It has been established that all visual content can be divided into three subgroups: structured, artistic, and demonstrative visual objects, which can be static or dynamic, in one plane or three-dimensional space. The impact of computer visualization on the methods of teaching general technical disciplines has been analysed. It has been shown that modern approaches to using computer visualization provide new opportunities for more effective and interactive learning, promoting the development of students’ technical and spatial imagination, which is crucial for future engineers and technical specialists. An approximate list of software for creating computer visualization tools, which can be useful in teaching general technical disciplines, has been provided. Among them are applications for creating presentations and infographics, 3D modelling, VR and AR-based applications and services, simulators, and emulators. The main directions for using computer visualization aids in teaching general technical disciplines are identified, including auxiliary synopsis, diagrams, tables, block diagrams, graphs, frames, word clouds, domain structures, memory cards, comics, heuristic sketches, knowledge animation, infographics, multimedia presentations, educational videos, static and dynamic 2D and 3D models, VR and AR objects. It has been concluded, that the didactic effectiveness of computer visualization in teaching general technical disciplines is ensured by certain provisions, namely: the focus on the quick and complete memorization of studied concepts, theories, and ideas by students; adherence to the principles of reliability, quality, completeness, sufficiency, logic, simplicity of perception, optimality, unity of graphics and text, and emphasis on key points; encouraging students to independently analyse and construct new, non-trivial didactic tasks allowing them to explore concepts, phenomena, or objects in terms of independent search and educational experimentation.